Rule-Based Versus Discretionary Fiscal Policy - Grabia, Tomasz (Olsztyn Economic Journal, 2016)
Fiscal policy can be of a discretionary or rule-based nature. This article discuses selected examples of fiscal rules as well as presents the advantages and disadvantages of following them. The aim of the article is to solve dilemmas about the positive and negative consequences of strict regulations of contemporary fiscal policy. Therefore, a hypothesis is tested concerning whether the following of rules in macroeconomic policy is a more beneficial solution than carrying out a discretionary policy. The hypothesis was not clearly verified. On the one hand, it was stated that it is usually more beneficial to follow standard rules due to higher reliability for markets. On the other hand, that entails lower flexibility, which may be especially disadvantageous during a crisis.